Automated Visual Tracking and Live Data Analysis in Badminton - Mona Teja K; Prabakaran N (International Journal of Advanced Science and Technology, 2020)
In the modern sports era, competition is all that matters. In order to compete in a sport, several strategies and analysis are required. Strategies against selected opponents can yield better results. But currently there is no such tool which gives the statistics without manual procedure